Polypoidal lesions of the gastrointestinal tract (Journal of Pathology of Nepal, 2020)
Background: With increasing usage of endoscopic procedures, gastrointestinal polypoidal lesions are commonly encountered specimens. Histopathological examination is crucial as biological behavior is dependent on its pathological nature.Materials and Methods: A retrospective descriptive study performed in Pathology department, Om Hospital and Research Centre from January 2017 to June 2019. The study included lesions received as polyp or polypoidal lesions of gastrointestinal tract for histopathological examination. Data was analysed using SPSS version 17.0. Gender, number and site were analysed using Chi square test to evaluate its association with neoplastic nature. Correlation with age and size was tested with Pearson’s correlation coefficient.Results: Among 150 cases of gastrointestinal tract polypoidal lesions, 58% were seen in male and 42% in female. Hyperplastic polyp and conventional adenoma were the commonest non-neoplastic and neoplastic lesions respectively. The age of patients ranged from 7 to 84 years with a mean age of 50 years. Rectosigmoid region was the commonest site. 134 patients had single and 16 had multiple polypoidal lesions. Most polypoidal lesion had size